Genotype‐sensitive reversible and time‐dependent CYP2D6 inhibition in human liver microsomes. Issue 2 (11th October 2018) - Storelli, Flavia; Desmeules, Jules; Daali, Youssef
Abstract: Cytochrome P450 (CYP) 2D6 metabolizes a wide range of xenobiotics and is characterized by a huge interindividual variability. A recent clinical study highlighted differential magnitude of CYP inhibition as a function of CYP2D6 genotype. The aim of this study was to investigate the effect of CYP2D6 genotype on the inhibition of dextromethorphan O‐demethylation by duloxetine and paroxetine in human liver microsomes (HLMs). The study focused on genotypes defined by the combination of two fully functional alleles (activity score 2, AS 2, n = 6), of one fully functional and one reduced allele (activity score 1.5, AS 1.5, n = 4) and of one fully functional and one non‐functional allele (activity score 1, AS 1, n = 6), which all predict extensive metabolizer phenotype. Kinetic experiments showed that maximal reaction velocity was affected by CYP2D6 genotype, with a decrease in 33% of V max in AS 1 HLMs compared to AS 2 ( P  = 0.06). No difference in inhibition parameters K i, K I and k inact was observed neither with the competitive inhibitor duloxetine nor with the time‐dependent inhibitor paroxetine. Among the genotypes tested, we found no difference in absolute CYP2D6 microsomal levels with ELISA immunoquantification. Therefore, our results suggest that genotype‐sensitive magnitude of drug‐drug interactions recently observed in vivo is likely to be due to differential amounts of functional enzymes at the microsomal level rather than to a difference in inhibition potencies across genotypes, which motivates for further quantitative proteomic investigations of functional and variant CYP2D6 alleles.